O projekcie słownika polskiego parlamentaryzmu XX WIEKU (lata 1918-2018): Etap wstępny – korpus parlamentarny - Szczyszek, Michał (Slavia Occidentalis, 2022)
The article discusses the preliminary results of research into the language corpus of the Polish parliamentary transcripts. Emphasis has been placed on a study of the emotional level of randomly selected transcripts. Two important lexemes (concept): niezawisłość and niepodległość have been studied by academics in terms of their use in transcripts. The frequency of these words has been estimated. Moreover, the semantic transformations of these words depending on the use of these lexemes in this discourse have been subjected to an academic study